Et sted å starte: Geografiske utforskninger av litteratur - Samoilow, Tatjana Kielland (Nordlit, 2022)
The article is a reflection over an experimental teaching sequence with students in Norwegian L1, autumn 2020. Departing from the field of literary geographies, we used geography as an analytical lens when reading the Swedish children's novel, The Murderer's Ape by Jakob Wegelius (2014). Our students mapped the geographical places in the novel on Padlet, they analyzed the visual maps included in the endpapers and discussed central settings in the novel. The experiment indicates that this analytic lens helps the students to read analytically, and it encourages critical reflections. However, we have to work more with enhancing close reading techniques. The teaching sequence was experimental and a part of a series of geographic explorations that aims at developing a geographical literary didactic. This didactic is meant to answer a problem posed by the new national curriculum, LK20: How can we enhance critical reading through explorative, cross disciplinary work with literature?